S-28-4: ASSOCIATION BETWEEN INCOME AND PROGRESSION OF CHRONIC KIDNEY DISEASE IN JAPAN: A NATIONWIDE COHORT STUDY. (January 2023) - Ishimura, Nana; Inoue, Kosuke; Kondo, Naoki
Abstract : Introduction: Chronic kidney disease (CKD) is one of the major public health issues, causing 1.4 million death in 2019 worldwide. While previous studies have shown the relationship between socioeconomic status and CKD, little is known about whether its relationship exists even in a country where insurance is comprehensively covered. Thus, we conducted a nationwide study to examine the association between individual income levels and the progression of CKD in Japan, a country with universal health coverage. Methods: We used the national database from the Japan Health Insurance Association (kyokai-kempo) between April 2015 and March 2021. We included 6, 318, 952 adults who undertook health check-ups in 2015 and had estimated Glomerular Filtration Rate (eGFR) measured at least twice during the study period. A multivariable linear regression model was used to investigate the association between income deciles and the average change in eGFR per year. A multivariable Cox proportional hazard regression model was used to estimate the hazard ratio [HR] for kidney replacement therapy (dialysis or kidney transplantation) according to deciles of individual income. We conducted the subgroup analysis by gender and prefectures. Results: The mean age was 48.8 years and 33.5 % were women. After adjusting for potential confounders, the lowest income group (bottom 10th percentile) showed a 0.08 [95%CI, 0.06–0.09] ml/min/1.73 m2/year larger decrease in eGFR than the highest income group (top 10th percentile). In our time-to-event analysis, we found an increased risk of kidney replacement therapy among the lowest income groups (HR [95%CI], 2.22 [1.99–2.48]) than among the highest income group. We found a similar pattern across gender and prefectures. Conclusion: Individual income levels were associated with the progression of CKD, particularly for the initiation of kidney replacement therapy in Japan. Our findings highlight the importance of considering socioeconomic status in CKD prevention and management even when insurance is covered.